Dancing to the Beat of Their Own Drum: Incorporating Art, Dance and Music as Culturally Relevant Pedagogy for Indigenous Students - Kennedy, Alysse (2016)
This research is an exploration into how a select group of educators in the TDSB are using art, dance and music as culturally relevant pedagogy for Indigenous students. This work has given insight into how to create relevant and meaningful educational experiences for First Nations, Métis and Inuit students, as well as how to transform “standard” classrooms to make academic success more accessible to these students. My research also explores the political implications of the government’s prioritization on aboriginal education, as well as the need for all teachers, regardless of their heritage, to serve as critical allies in order to decolonize education and promote an equitable and safe space for all students, and especially for Indigenous students. Themes explored include the importance of community partnerships and family connections, practical strategies for integrating arts-based education, the inherent connection to outdoor and place-based education, and the critical gains that can be made through using Indigenous story-telling traditions of art, dance and music as therapeutic, engaging and approachable avenues for realizing success in schools. Ultimately, my research proposes that self-identity cultivates self-efficacy, so as teachers we need to remember to celebrate culture within the classroom.